PLUMED: a portable plugin for free-energy calculations with molecular dynamics - Bonomi, M.; Branduardi, D.; Bussi, G.; Camilloni, C.; Provasi, D.; Raiteri, Paolo; Donadio, D.; Marinelli, F.; Pietrucci, F.; Broglia, R.; Parrinello, M. (Elsevier, 2009)
Here we present a program aimed at free-energy calculations in molecular systems. It consists of aseries of routines that can be interfaced with the most popular classical molecular dynamics (MD) codes through a simple patching procedure. This leaves the possibility for the user to exploit many different MD engines depending on the system simulated and on the computational resources available. Freeenergy calculations can be performed as a function of many collective variables, with a particular focus on biological problems, and using state-of-the-art methods such as metadynamics, umbrella sampling and Jarzynski-equation based steered MD. The present software, written in ANSI-C language, can be easily interfaced with both Fortran and C/C++ codes.